PENERAPAN PRINSIP DEMOKRASI EKONOMI, KEADILAN DAN KEPASTIAN HUKUM DALAM HUKUM PENANAMAN MODAL - Ronny Winarno (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2005)
System of Perekomonian Indonesia embrace the Economic Democracy under colour of familiarity ground affirmed in Section 33 article 4 UUD 1945 (after amandemen) the executed principally is togetherness, efficiency with justice have, continuation, with vision of environment, independence, and also by balancing economic union and progress national, thereby prosperity do not just to individual or group of people but for all people.